Characterization of Senegalese sole (Solea senegalensis) Mx promoter - Carballo Perez, Carlos; Alonso-Sánchez, María del Carmen; Collet, Bertrand; Béjar-Alvarado, Julia; Álvarez-Torres, Daniel; García-Rosado, Esther (Elsevier, 2013)
Type I interferon (IFN) represents a first component of the innate immune response against viral infections, promoting an antiviral state in cells. Mx proteins are the best studied IFN-inducible genes (ISGs) in fish. The antiviral activity against different fish viruses has been demonstrated for diverse fish Mx proteins, including Senegalese sole (Solea senegalensis) Mx protein (SsMx). To advance in the knowledge on the IFN pathway and the antiviral state in this species, is necessary to understand the regulatory mechanisms determining ISGs transcription. For this reason, the aim of the current study was the cloning and functional characterization of the SsMx promoter. To fulfill this objective, GenomeWalkerTM Universal Kit was used to clone the SsMx promoter. A fragment of 1327 bp upstream of the transcriptional start site has been obtained. Sequence analysis showed a typical structure of an ISG promoter, including three ISREs (Interferon stimulated response element), a gamma activation sequence (GAS), a SP1 binding site, a STAT binding site and typical GAAA/TTTC boxes. Then, the 1327-bp fragment obtained was cloned into a luciferase reporter vector, which was transfected into RTG-2 and CHSE-214 cells. The expression of the luciferase was measured at different time points after stimulation of the IFN pathway with poly I:C. Interestingly, luciferase expression patterns differed depending of the cell line considered. In RTG-2 cells, the highest level of luciferase expression was observed at 24-48 h post-induction (p.i), decreasing afterwards, whereas in CHSE-214 cells a gradual increase of the luciferase expression up to 72 h p.i. was observed. Deletion and punctual mutation analyses have been performed to determinate the contribution of each ISRE in the inducibility of the SsMx promoter. Results show that the ISRE1, sited closest to the transcriptional start site, is the main element contributing to the SsMs promoter response, while both, ISRE2 and ISRE3, have a minor additive effect on the activity of the SsMx promoter induction.
Keywords: Peces - Inmunología; Solea senegalensis; Mx promoter; Interferon; ISRE